The dynamics of a one-dimensional parabolic problem versus the dynamics of its discretization - Bruschi, S. M.; Carvalho, A. N.; Ruas, J. G. (Academic Press Inc., 2000)
In this paper we prove that the spatial discretization of a one dimensional system of parabolic equations. with suitably small step size, contains exactly the same asymptotic dynamics as the continuous problem. (C) 2000 Academic Press.
Keywords: parabolic equations; spatial discretization; topological equivalence of attractors